Zinc oxide for electronic, photovoltaic and optoelectronic applications - Godlewski, M.; Guziewicz, E.; Kopalko, K.; Łuka, G.; Łukasiewicz, M.I.; Krajewski, T.; Witkowski, B.S.; Giera╕towska, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We demonstrate that the atomic layer deposition (ALD) technique has large potential to be widely used in aproduction of ZnO films for applications in electronic, photovoltaic (PV) and optoelectronic devices. Low growth temperature makes the ALD-grown ZnO films suitable for construction of various semiconductor/organic material hybrid structures. This opens possibilities of construction of novel devices based on very cheap organic materials. This includes organic light emitting diodes and PV cells of the third generation, as discussed in the present work.